Synthesis and characterization of new aromatic polyesters containing pendent naphthyl units - Honkhambe, Pandurang N.; Biyani, Mahesh V.; Bhairamadgi, Nagendra S.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (Journal of Applied Polymer Science, 2010)
Two bisphenols, viz., 4,4'-[1-(2-naphthaleny-1)ethylidene]bisphenol and 4,4'-[1-(2-naphthalenyl) ethylidene]bis-3-methylphenol were prepared by condensation of commercially available 2-acetonaphthanone with phenol and o-cresol, respectively. A series of new aromatic polyesters containing pendent naphthyl units was synthesized by phase-transfer-catalyzed interfacial polycondensation of these bisphenols with isophthaloyl chloride, terephthaloyl chloride, and a mixture of isophthaloyl chlorideiterephthaloyl chloride (50 : 50 mol %). Inherent viscosities of polyesters were in the range 0.83-1.76 dL g(-1), while number average molecular weights (M(n)) were in the range 61,000-235,000 g mol(-1). Polyesters were readily soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, m-cresol, pyridine, N,N-dimethylformamide, N,N-dimethylacetarnide, and 1-methyl-2-pyrrolidinone at room temperature. Tough, transparent, and flexible films were cast from a solution of polyesters in chloroform. X-Ray diffraction measurements displayed a broad halo at 20 congruent to 19 degrees indicating the amorphous nature of polyesters. Glass transition temperatures of polyesters were in the range 209-259 degrees C. The temperature at 10% weight loss (T(10)), determined by TGA in nitrogen atmosphere, of polyesters was in the range 435-500 degrees C indicating their good thermal stability. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 117: 2545-2552, 2010
Keywords: Aromatic polyesters; bisphenol; interfacial polycondensation; pendent naphthyl units

Synthesis and characterization of new aromatic polyesters containing cardo decahydronaphthalene groups - Honkhambe, Pandurang N.; Bhairamadgi, Nagendra S.; Biyani, Mahesh V.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (European Polymer Journal, 2010)
Three cardo bisphenols containing decahydronaphthalene group viz., 4,4'-(octahydro-2(1H)-naphthylidene)bisphenol, 4,4'-(octahydro-2(1H)-naphthylidene)bis-3-methylphenol and 4,4'-(octahydro-2(1H)-naphthylidene)bis-3,5-dimethylphenol were synthesized starting from commercially available 2-naphthol and were utilized for synthesis of new aromatic polyesters by phase transfer-catalyzed interfacial polycondensation with isophthaloyl chloride, terephthaloyl chloride and a mixture of isophthaloyl chloride and terephthaloyl chloride (50:50 mol %). Inherent viscosities and number average molecular weights (M(n)) of polyesters were in the range 0.35-0.84 dL/g and 13300-48,500 (Gel Permeation Chromatography, polystyrene standard), respectively. Polyesters were readily soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, meta-cresol, pyridine, N,N-dimethylformamide, N,N-dimethylacetamide, and 1-methy1-2-pyrrolidinone at room temperature and could be cast into tough, transparent and flexible films from their chloroform solutions. Wide-angle X-ray diffraction measurements revealed the amorphous nature of polyesters. The glass transition temperature of polyesters was in the range 207-287 degrees C. The temperature at 10% weight loss (T(10)), determined from thermogravimetric analysis of polyesters, was in the range 425-460 degrees C indicating their good thermal stability. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: bisphenol; Cardo; Decahydronaphthalene; polyester; Structure-property relationship